Predominance of Cand. Patescibacteria in Groundwater Is Caused by Their Preferential Mobilization From Soils and Flourishing Under Oligotrophic Conditions - Herrmann, Martina; Wegner, Carl-Eric; Taubert, Martin; Geesink, Patricia; Lehmann, Katharina; Yan, Lijuan; Lehmann, Robert; Totsche, Kai Uwe; Küsel, Kirsten (Frontiers in Microbiology, 2019)
Despite the widely observed predominance of Cand. Patescibacteria in subsurface communities, their input source and ecophysiology are poorly understood. Here we study mechanisms of the formation of a groundwater microbiome and the subsequent differentiation of Cand. Patescibacteria. In the Hainich Critical Zone Exploratory, Germany, we trace the input of microorganisms from forested soils of preferential recharge areas through fractured aquifers along a 5.4 km hillslope well transect. Cand. Patescibacteria were preferentially mobilized from soils and constituted 66% of species-level OTUs shared between seepage and shallow groundwater. These OTUs, mostly related to Cand. Kaiserbacteraceae, Cand. Nomurabacteraceae, and unclassified UBA9983, represented a relative abundance of 71.4% of the Cand. Patescibacteria community at the shallowest groundwater well, and still 44.4% at the end of the transect. Several Cand. Patescibacteria subclass-level groups exhibited preferences for different conditions in the two aquifer assemblages investigated: Cand. Kaiserbacteraceae surprisingly showed positive correlations with oxygen concentrations, while Cand. Nomurabacteraceae were negatively correlated. Co-occurrence network analysis revealed a central role of Cand. Patescibacteria in the groundwater microbial communities and pointed to potential associations with specific organisms, including abundant autotrophic taxa involved in nitrogen, sulfur and iron cycling. Strong associations among Cand. Patescibacteria themselves further suggested that for many groups within this phylum, distribution was mainly driven by conditions commonly supporting a fermentative life style without direct dependence on specific hosts. We propose that import from soil, and community differentiation driven by hydrochemical conditions, including the availability of organic resources and potential hosts, determine the success of Cand. Patescibacteria in groundwater environments.